Physico-chemical analysis of biodiesel obtained from blends of virgin castor oil and waste frying oil - Guimarães, Daniela Helena Pelegrine (2019)
Fil: Guimarães, Daniela Helena Pelegrine. University of Sao Paulo. Lorena Engineering School; Brasil.